Utility of Dissociated Intrinsic Hand Muscle Atrophy in the Diagnosis of Amyotrophic Lateral Sclerosis - Menon, Parvathi (MyJove Corporation, 2014)
The split hand phenomenon refers to predominant wasting of thenar muscles and is an early and specific feature of amyotrophic lateral sclerosis (ALS). A novel split hand index (SI) was developed to quantify the split hand phenomenon, and its diagnostic utility was assessed in ALS patients. The split hand index was derived by dividing the product of the compound muscle action potential (CMAP) amplitude recorded over the abductor pollicis brevis and first dorsal interosseous muscles by the CMAP amplitude recorded over the abductor digiti minimi muscle. In order to assess the diagnostic utility of the split hand index, ALS patients were prospectively assessed and their results were compared to neuromuscular disorder patients. The split hand index was significantly reduced in ALS when compared to neuromuscular disorder patients (P<0.0001). Limb-onset ALS patients exhibited the greatest reduction in the split hand index, and a value of 5.2 or less reliably differentiated ALS from other neuromuscular disorders. Consequently, the split hand index appears to be a novel diagnostic biomarker for ALS, perhaps facilitating an earlier diagnosis.